A FRET biosensor reveals spatiotemporal activation and functions of aurora kinase A in living cells - Giulia Bertolin (Nature Portfolio, 2016)
Alterations in aurora kinase A (AURKA) activity can result in mitotic errors and have been associated with cancer progression. Here the authors develop a FRET biosensor which functionally replaces AURKA in cells, and show that its activation in the G1 phase is required to maintain microtubule stability.